SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT KULIT PADA MANUSIA SERTA PENGOBATANNYA MENGGUNAKAN TANAMAN OBAT BERBASIS WEB - Alfiandri -; Suraya -; Erfanti Fatkhiyah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Health is a valuable thing for human beings, because anyone can experience health problems. Skin disease is a disease that affects humans in daily life due to lack of awareness of self or environment, hygiene, which are caused by climatic factors, the environment, housing, unhealthy living habits, allergies, pets and others. Since ancient times the people of Indonesia have recognized and utilize medicinal plants as one of the efforts in the prevention of health problems that it faces. The use of plants as medicines in Indonesia also has lasted thousands of years ago. Medicinal plants have the property to cure various diseases. One of the curable disease is a skin disease. The purpose of this research is to design and build an expert system to determine the types of skin diseases based web that can assist users in determining the types of skin diseases based on physical characteristics and symptoms or complaints to the discovery of advice on the treatment of information regarding skin disease along with solutions treatment using medicinal plants. In this study, using the method of Forward Chaining, and Certainty Factor. Wherein Forward Chaining method as the tracking process while the Certainty Factor method is a way to measure whether or not a fact that surely must have in diagnosing the disease.This research has produced a diagnostic expert system with the skin disease treatment solutions using web-based medicinal plants that can diagnose the disease through the symptoms and then provide the solution of any disease.